PENGARUH KESADARAN ETIKA DIGITAL TERHADAP CIVIC BEHAVIOR MAHASISWA PPKN UNIVERSITAS LAMPUNG - Annisa Salsabila Azzahra; Berchah Pitoewas; Nurhayati Nurhayati; Devi Sutrisno Putri; Rohman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine and analyze the influence of digital ethics awareness on the civic behavior of students of the Pancasila and Citizenship Education (PPKn) Study Program at the University of Lampung. The research method used in this study is a descriptive method with a quantitative approach. The subjects of this study were PPKn students at the University of Lampung from 2022 to 2024 with a sample of 76 respondents. The data collection technique used a questionnaire and was strengthened by interview techniques. Based on the results of the study, it shows that digital ethics awareness influences the civic behavior of PPKn students at the Faculty of Teacher Training and Education, University of Lampung. Based on a simple linear regression test, the RSquare value obtained was 0.109. This indicates that digital ethics awareness contributes 10.9% to the formation of student civic behavior, while the remaining 89.1% is influenced by other factors outside this research variable. The meaning of this 10.9% figure indicates that knowledge and internalization of digital ethical values ​​​​of PPKn students at the University of Lampung have become the basic foundation for behaving in the digital space. However, this low percentage also reveals the reality that digital citizenship behavior (civic behavior) is a very complex phenomenon and does not only depend on the normative understanding of individuals alone.